Embedded performance validity indicator for children: California Verbal Learning Test – Children's Edition, forced choice. Issue 3 (3rd July 2019) - Verroulx, Kristin; Hirst, Rayna B.; Lin, George; Peery, Shelley
ABSTRACT: Performance validity testing in children undergoing neuropsychological testing is a growing research area. Accurate identification of performance validity is necessary to avoid invalid assessment conclusions. In the present research, a forced choice (FC) trial was created for the California Verbal Learning Test – Children's Edition (CVLT-C), modeled after the established California Verbal Learning Test – Second Edition (CVLT-II) FC trial. Distractor words were taken directly from the CVLT-II FC Standard Form, with about half being concrete (n = 8) and half abstract (n = 7). The order of the items was organized similarly to the CVLT-II FC to ensure that items from within the same category were not sequential. The Test of Memory Malingering was administered for comparison, and three embedded measures that have previously been validated in adults were also calculated. The CVLT-C FC trial was administered to 40 children, aged 6–16 (M = 12.08, SD = 3.13). Average full scale IQ was 97.3 (SD = 12.41, range = 71–123). Ninety-three percent of examinees performed perfectly on the CVLT-C FC, suggesting high specificity, which is similar to findings for the CVLT-II FC normative group (90%). Results from other embedded measures are also presented.